Computerisation of Public Administration in Slovakia – Impact on (the Fiscal Position of ) Municipalities - Románová, Anna; Červená, Karolína (Public Governance, Administration and Finances Law Review, 2019)
The authors of the paper will analyse the structure of revenues and expenditures of local governments and evaluate the actual level of their independence. The authors will try to identify the room for improving of the financial position of the municipalities and special attention will be paid to a certain means of rationalisation of public administration, particularly computerisation within the e-Government projects that should, inter alia, lead to reduction of the administrative burden laid upon (local) government bodies and also saving of the budget. The analysis, largely based on a survey conducted by the authors within primary research, shows that performance of reforms in terms of rationalisation efforts may be a way forward, hence, the one analysed in this paper was not implemented in a fully satisfactory manner.